Genetic etiological analysis of auditory neuropathy spectrum disorder by next-generation sequencing - Sun, Lianhua; Lin, Zhengyu; Zhang, Jifang; Shen, Jiali; Wang, Xiaowen; Yang, Jun (Frontiers in Neurology, 2022)
Objective: Auditory neuropathy spectrum disease (ANSD) is caused by both environmental and genetic causes and is defined by failure in peripheral auditory neural transmission of normal outer hair cells. Up to now, 13 genes identified as potentially causing ANSD have been documented. In order to study the etiology of ANSD, we collected 9 probands with ANSD diagnosed in the clinic and performed targeted next-generation sequencing. Methods: Nine probands have been identified as ANSD based on the results of the ABR tests and DPOAE/CMs. Genomic DNA extracted from their peripheral blood was examined by NGS for a gene panel, and targeted next-generation sequencing was used to identify any potential causal variations. For candidate pathogenic genes, we performed co-segregation among all family members of the pedigrees. Subsequently, using mini gene assay, we examined the function of a novel mutant splice site of OTOF. Results: We analyzed nine cases of ANSD patients with normal CMs/DPOAE and abnormal ABR, discovered three novel mutant sites of OTOF gene that are known to cause ANSD, and six cases of other gene mutations including TBC1D24, LARS2, TIMM8A, MITF, and WFS1. Conclusion: Our results extend the mutation spectrum of the OTOF gene, and indicate that the genetic etiology of ANSD may be related to gene mutations of TBC1D24, LARS2, TIMM8A, MITF, and WFS1.